2002
DOI: 10.1128/iai.70.9.5086-5090.2002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Cross-Reactivity and Cross-Protection Elicited by Immunization with DNA Vaccines against Streptococcus pneumoniae Expressing PspA Fragments from Different Clades

Abstract: Streptococcus pneumoniae is a major cause of disease, especially in developing countries, and cost-effective alternatives to the currently licensed vaccines are needed. We constructed DNA vaccines based on pneumococcal surface protein A (PspA), an antigen shown to induce protection against pneumococcal bacteremia. PspA fragments can be divided into three families, which can be subdivided into six clades, on the basis of PspA amino acid sequence divergence (S. K. Hollingshead, R. Becker, and D. E. Briles, Infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 16 publications
1
37
2
6
Order By: Relevance
“…Nevertheless, cross-protection against family 2 strains was also dependent on the PspA clade; PspA1ABC-3AB was protective against the PspA3-containing strain, and anti-PspA1ABC-4B was protective against the PspA4-containing strain. Previous studies in our laboratory have shown that cross-reactivity of antibodies induced by DNA vaccination is restricted to the same family, while cross-protection against intraperitoneal challenge is restricted to the same clade (16). These similarities suggest that PspA hybrids are able to broaden protection when presented as either recombinant proteins or as DNA.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Nevertheless, cross-protection against family 2 strains was also dependent on the PspA clade; PspA1ABC-3AB was protective against the PspA3-containing strain, and anti-PspA1ABC-4B was protective against the PspA4-containing strain. Previous studies in our laboratory have shown that cross-reactivity of antibodies induced by DNA vaccination is restricted to the same family, while cross-protection against intraperitoneal challenge is restricted to the same clade (16). These similarities suggest that PspA hybrids are able to broaden protection when presented as either recombinant proteins or as DNA.…”
Section: Discussionmentioning
confidence: 63%
“…All cloning procedures were performed with Escherichia coli DH5␣ grown in Luria-Bertani medium supplemented with ampicillin (100 g/ml). DNA fragments encoding portions of the N-terminal regions of PspA clades 1, 3, and 4 were amplified by PCR from pTG-pspA1-4 or pTG-pspA3-2 (16). The primers used in this procedure are listed in Table1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous results showed that protective Th1 immune responses against pneumococcal infection in a mouse model can be achieved successfully by DNA vaccines using vectors expressing PspA (8,17). The PspA fragment used in this study comprises the N-terminal region through the prolinerich region without the signal sequence from a clade 3 (family 2) PspA and is expressed in a secreted form by a DNA vaccine vector (pSec-pspA3NS).…”
mentioning
confidence: 99%